Supplemental chromium and revaccination effects on performance and health of newly weaned calves - S.A. Lindell; Robert T. Brandt Jr.; J. Ernest Minton; Frank Blecha; Gerald L. Stokka; C.T. Milton (Kansas Agricultural Experiment Station Research Reports, 1994)
Two trials were conducted to evaluate the effects of chromium (Cr) supplementation (4 mg/hd/day in a yeast form) or no supplementation, with or without revaccination with a modified live viral vaccine at 9 days postweaning o n performance, health, and ability to withstand an IBR challenge infection. In Trial 1, Cr supplementation had no effect on performance of newly weaned calves in a 28-day receiving study, but reduced the incidence of respiratory disease by 37%. Revaccinati on depressed dry matter intake and had no effect on animal health. In trial 2, blood plasma levels of cortisol and ACTH (stress hormones ) were measured at 6 and 26 days postweaning. Cortisol levels were unaffected by treatment or by time after weaning. Plasma ACTH conc e ntrations were lower at 26 vs 6 days postweaning, and were reduced at 26 days by revaccination. Despite some slight differences in rectal temperature, treatment did not appear to affect the animals' ability to withstand a live IBR challenge. We concluded that supplemental Cr was beneficial in reducing the incidence of bovine respiratory disease, although mediation of stress hormones was not involved. Revaccination of newly weaned calves with a modified live viral vaccine showed no performance or health benefit.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Chromium; Weaned calves; Respiratory disease